Participatory Action Research, Critical Adult Education, and the Work of D. E. Smith for Research Praxis: Lessons from/with Young Adults Experiencing Homelessness - Malenfant, Jayne; Nichols, Naomi (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2024)
From 2017-2021, the Youth Action Research Revolution (YARR) team documented the institutional histories of young people experiencing homelessness in Canada. Interviews with youth focused on educational, child welfare, healthcare, and criminal justice institutions. Situated at the intersections of critical adult education (CAE), participatory action research (PAR), and Institutional Ethnography (IE), we outline our mobilization of IE to ground learning and action within our team. We document the different phases of learning that we undertook, as a means of illustrating how CAE, PAR, and IE can be mutually supportive frameworks for praxis and activist learning. We highlight our use of IE to bring illuminate and resist the institutionalizing processes at work in post-secondary contexts and reflect on the importance of mutual aid as essential to realizing the social justice potential of participatory research. We suggest that co-creating IE research with young adults with lived experiences of homelessness constitutes a unique opportunity to mobilize CAE values and tangibly support community research that seeks to positively influence the lives of those implicated by the problems we study together.